Implikasi Pertumbuhan Penduduk dan Alih Fungsi Lahan Sawah terhadap Ketahanan Pangan di Provinsi Gorontalo - Usman, Mohamad Zainudin; Lihawa, Fitriyane; Baderan, Dewi Wahyuni K. (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study investigates the implications of population growth and the conversion of paddy fields on rice food security in Gorontalo Province, Indonesia, during 2018–2023. Employing a quantitative descriptive research design with panel regression analysis, the research examines the relationship between population growth, paddy field conversion, and rice food security as a dependent variable. The findings reveal that both population growth and paddy field conversion significantly and positively influence rice food security. Population growth raises demand for rice, while paddy field conversion threatens production capacity, intensifying food security challenges. The results suggest that addressing land-use changes and managing population growth are crucial for maintaining sustainable food availability. This study contributes to understanding the dynamics of food security and provides recommendations for policymakers to design effective strategies in balancing population needs, agricultural sustainability, and economic development in Gorontalo.